Ett reformerat prospektansvar - Särskilt om skadeståndsansvar för juridiska personer och bedömningen av orsakssamband - Svantesson,Per (2014)
This paper aims to provide a detailed analysis of the Swedish prospectus liability from a tort law perspective, focusing on the liability for legal persons as well as the proposed reforms of the prospectus liability in Ds 2013:16. A prospectus shall contain essential information regarding the issuer and the securities, in order for an investor to be able to perform an informed assessment of the applicable issuer as well as the relevant securities. Therefore, if inaccurate or incomplete information is introduced in a prospectus, company members, including the CEO, members of the board or the founders may be liable for damages, in accordance with the general tort law rules in the Liability for Damages Act or the special tort liability provisions of the Companies Act. However, it is not possible to impose prospectus liability on legal persons according to current law. It is also uncertain how causation in regard to prospectus liability shall be assessed, under current law. In order to modernize and harmonize the Swedish prospectus liability with the EU rules, the legislator presents reform proposals in a memorandum. The purpose of the reforms is, according to the legislator, to clarify the prospectus liability particularly in regard to legal persons. Consequently, the legislator provides that prospectus liability shall be imposed on legal persons and that the liability for company members shall be limited, to some extent. In addition, the legislator proposes that only those who actively acquire securities, due to inaccurate or incomplete information, shall be entitled to compensation. Regarding causation the legislator provides that this issue will have to be decided by the courts. In my opinion, a reform of the Swedish prospectus liability is necessary. Firstly, I believe it is beneficial that a legal person is proposed to be liable for inaccurate or incomplete information in a prospectus. However, the liability of legal persons shall, according to my opinion, be limited to the company’s shareholders equity. Secondly, I believe that it is unreasonable that the legislator retains the extensive liability provisions regarding company members. Instead, the liability of the company members' shall be limited to a secondary liability in relation to the liability of legal persons, according to me. Moreover, I believe that the legislator does not meet the purpose of the reformed prospectus liability, which is to clarify the provisions, especially regarding legal persons. As to causation, I believe that the standard protection doctrine in addition to the proximate cause is the most appropriate solution.
Keywords: law; associationsrätt; civilrätt; private law; skadeståndsrätt; tort law; fiscal law; prospektansvar; prospekt; aktiemarknadsrätt; aktiebolag; skadeståndsansvar; prospectus; liability.